(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
The article highlights the main ideas of the late nineteenth and early twentieth centuries in the socio-philosophical views of our people related to the Enlightenment and its new stage, Jadidism. The spiritual heritage of the Bukhara enlighteners has been philosophically analyzed.